Anti-slip sewage-resistant waterborne coating and preparation method thereof
By combining emulsion-type silicone aqueous dispersion resin, maleic anhydride-grafted polypropylene wax emulsion, and elastomer-modified acrylic dispersion, and combining with water-based isocyanate curing agent to form a cross-linked network structure, the problems of insufficient anti-slip, stain resistance, and adhesion of water-based tableware coatings are solved, and the application of high-performance environmentally friendly coatings is realized.
Patent Information
- Application Number
- CN202511366883.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-24
- Publication Date
- 2025-10-31
- Estimated Expiration
- 2045-09-24
AI Technical Summary
Existing water-based tableware coatings are inadequate in terms of anti-slip properties, stain resistance, and adhesion. Furthermore, they are prone to peeling and discoloration under high-temperature cleaning conditions, failing to meet consumers' demands for durable and easy-to-clean tableware.
The coating employs a composite of emulsion-type silicone aqueous dispersion resin, maleic anhydride-grafted polypropylene wax emulsion, and elastomer-modified acrylic dispersion, combined with a water-based isocyanate curing agent to form a cross-linked network structure, enhancing the coating's anti-slip properties, wear resistance, and adhesion. Furthermore, the surface microstructure is optimized through nano-scale alumina dispersion, and the addition of emulsified corrugation additives improves both aesthetics and anti-slip performance.
It achieves high adhesion, anti-slip and stain resistance. The coating is stable in mechanical cleaning environments, meets food contact material standards, has excellent stain resistance and easy cleaning performance, and reduces VOC emissions.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention relates to the field of tableware coating technology, specifically to an anti-slip and water-resistant coating and its preparation method. Background Technology
[0002] Plastic tableware and catering utensils (such as trays) have become an important solution in the food packaging and catering service industries due to their lightweight, durability, and low cost. However, traditional plastic substrates have inherent defects: their low surface energy results in insufficient water and oil resistance, especially when in contact with oily or high-moisture foods, which can easily lead to penetration, causing tableware deformation, contamination, and even food safety hazards. To improve functionality, the industry generally adopts surface coating technology, which involves applying special coatings to plastic substrates (such as PP and PS) to enhance hydrophobicity, oleophobicity, abrasion resistance, and ease of cleaning.
[0003] Traditional tableware coatings are mostly solvent-based. For example, Chinese patent application CN201911384689.1 discloses an anti-slip and stain-resistant tableware paint, which consists of polyester resin, long-grafted organosilicon anti-stain leveling agent, organotin drier, and solvent (ethyl acetate or n-butyl acetate), exhibiting excellent chemical resistance and stain resistance. However, these coatings release large amounts of volatile organic compounds (VOCs) during production and use, causing environmental pollution and posing a potential threat to the health of production personnel and consumers. With increasingly stringent global environmental regulations and a significant increase in public environmental awareness, the market demand for environmentally friendly tableware coatings with low VOC emissions has become extremely urgent. Water-based coatings, due to their environmental advantages of using water as the main dispersion medium and having low VOC content, are considered an ideal alternative.
[0004] However, current water-based tableware coatings on the market face a series of interconnected key performance defects in practical applications, severely restricting their widespread adoption and user satisfaction. Some coatings lack sufficient anti-slip properties, causing tableware placed on plates to easily slip and spill food, posing a safety hazard such as burns. Furthermore, their resistance to stains and sauce seepage is unsatisfactory; common stains such as soy sauce and chili oil are difficult to clean thoroughly, and pigments can easily penetrate the coating, forming stubborn spots and damaging the product's appearance. In addition, existing water-based coatings generally have poor adhesion to plastic substrates. Repeated use or mechanical cleaning (such as high-temperature, high-pressure water jets in dishwashers and cleaning environments with strong alkaline detergents) can easily lead to problems such as blistering, cracking, peeling, discoloration, and loss of gloss, resulting in functional failure and accelerating microplastic release, failing to meet consumers' core needs for durable and easy-to-clean tableware.
[0005] Therefore, developing a high-performance water-based environmentally friendly coating that can simultaneously achieve excellent anti-slip properties, stain resistance, and strong adhesion to plastic substrates has significant technical value and urgent practical significance in the tableware manufacturing industry. Summary of the Invention
[0006] To overcome the shortcomings of the existing technology, the present invention aims to provide a water-based coating that can achieve excellent anti-slip effect, stain resistance and strong adhesion to plastic substrates.
[0007] This invention is achieved through the following technical solution: In a first aspect, the present invention provides an anti-slip and water-resistant coating, comprising liquid A and liquid B; The A liquid, by weight, comprises the following components: 35-60 parts of emulsion-type silicone aqueous dispersion resin; 3-10 parts of maleic anhydride-grafted polypropylene wax emulsion; 5-10 parts of elastomer-modified acrylic dispersion; 0.5-1.2 parts of dispersant; 1-3 parts of thickener; 3-8 parts of nano-alumina dispersion; 15-25 parts of water-based color paste; 0.3-1 part of emulsifying ripple agent; 0.1-1 part of substrate wetting agent; 0.1-1 part of defoamer; and 3-5 parts of deionized water. The B liquid comprises, by weight, the following components: 90-100 parts of water-based isocyanate curing agent, 0.3-0.8 parts of dehydrating agent, 5-8 parts of adhesion promoter, and 2-5 parts of film-forming aid.
[0008] This invention provides an innovative two-component waterborne coating system. Through the synergistic effect of the components after mixing liquid A and liquid B, it comprehensively addresses the multiple requirements of tableware for coatings that offer anti-slip properties, stain resistance, adhesion, and environmental friendliness. Liquid A is a composite of an emulsion-type silicone aqueous dispersion resin, maleic anhydride-grafted polypropylene wax emulsion, and elastomer-modified acrylic dispersion. The emulsion-type silicone aqueous dispersion resin forms a flexible and temperature-resistant base for the coating, endowing it with excellent hydrophobicity and low surface energy, achieving stain resistance and easy cleaning. The active hydroxyl groups of the elastomer-modified acrylic dispersion provide key cross-linking reaction sites for the system, while significantly enhancing the coating's impact toughness and substrate adhesion. The maleic anhydride-grafted polypropylene wax emulsion forms a uniform micro-rough structure on the coating surface after film formation. This significantly increases the coefficient of friction and improves the anti-slip effect. The water-based isocyanate curing agent in liquid B undergoes a cross-linking reaction with the active hydroxyl groups in liquid A, forming a dense three-dimensional network structure, effectively improving the coating's hardness, wear resistance, and chemical resistance. Simultaneously, the addition of emulsifying ripple additives gives the paint film a unique textured effect, enhancing its aesthetics while further improving its anti-slip performance by increasing the contact area. Nano-sized alumina dispersion, as a nano-reinforcing phase, synergistically optimizes the surface microstructure with wax microparticles, jointly enhancing impact resistance and anti-slip performance. Furthermore, dispersants and defoamers ensure the storage stability and film density of each component, while substrate wetting agents effectively reduce the system's surface tension, guaranteeing excellent wetting and adhesion to plastic substrates.
[0009] Furthermore, the solid content of the emulsion-type silicone aqueous dispersion resin is 36%-40%. As a preferred embodiment, the emulsion-type silicone aqueous dispersion resin of the present invention is KW-8924 from Kehuai Industrial (Shanghai) Co., Ltd.
[0010] Furthermore, the solid content of the maleic anhydride-grafted polypropylene wax emulsion is 34%-42%. As a preferred embodiment, the maleic anhydride-grafted polypropylene wax emulsion of the present invention is Michael Men's Emulsion 94340.
[0011] Furthermore, the hydroxyl value of the elastomer-modified acrylic dispersion is 100-120 mgKOH / g. As a preferred embodiment, the elastomer-modified acrylic dispersion of the present invention is SX-500-2 from Kunshan Wanjie New Material Technology Co., Ltd.
[0012] Further, the dispersant is selected from an aqueous solution of polyether-modified styrene-maleic anhydride copolymer; the solid content of the aqueous solution of polyether-modified styrene-maleic anhydride copolymer is 35%-45%. As a preferred embodiment, the dispersant of the present invention is DISPERBYK-190 from BYK Chemicals.
[0013] Furthermore, the thickener is selected from hydrophobic modified alkali-swellable thickeners. As a preferred embodiment, the thickener is H-120 thickener from Puwei (Shanghai) New Material Technology Co., Ltd.
[0014] Furthermore, the particle size D50 of the nano-alumina dispersion is 120-150 nm, and the solid content is 30%-40%. As a preferred embodiment, the nano-alumina dispersion of the present invention is selected from TAD-HA30 and TAD-HA40 of Nanjing Tianxing New Materials Co., Ltd.
[0015] Furthermore, the aqueous colorant is selected from food contact grade aqueous colorants, with a solid content of 40%-60%.
[0016] The water-based pigment of this invention can be obtained commercially or by self-production. This invention provides a method for preparing the water-based pigment, comprising the following steps: S1. Add water, dispersant, and defoamer, and disperse evenly at 300-500 rpm; S2. Add food-grade pigment powder while stirring at 200-300 rpm, and increase the speed to 500-700 rpm to disperse evenly; S3. After evenly dispersing, increase the rotation speed to 800-1000 rpm and disperse for at least 30 minutes; S4. Transfer to a horizontal grinder and grind to a fineness of <15μm; S5. Add stabilizer and adjust the viscosity of the color paste with water to the required solid content range.
[0017] Furthermore, the emulsifying corrugation aid is an organosilicon polymer emulsion. As a preferred embodiment, the emulsifying corrugation aid of the present invention is selected from HY-8082 of Haiyue (Qingyuan) New Materials Co., Ltd.
[0018] Furthermore, the substrate wetting agent is selected from polyether siloxane copolymers. As a preferred embodiment, the substrate wetting agent of the present invention is TEGO's Wet 270.
[0019] Further, the defoamer is selected from a polyether siloxane copolymer emulsion containing fumed silica; the mass content of the polyether siloxane copolymer in the polyether siloxane copolymer emulsion containing fumed silica is 15%-25%. As a preferred embodiment, the defoamer of the present invention is TEGO's Airex 902 W.
[0020] Furthermore, the NCO content of the aqueous isocyanate curing agent is 16%-18%. As a preferred embodiment, the aqueous isocyanate curing agent of the present invention is selected from AQUAPU-379 of Jiangsu Fuqisen New Material Co., Ltd.
[0021] Furthermore, the dehydrating agent is selected from titanate dehydrating agents or molecular sieve dehydrating agents.
[0022] Furthermore, the adhesion promoter is selected from γ-(2,3-epoxypropoxy)propyltrimethoxysilane (KH560).
[0023] Furthermore, the film-forming aid is selected from one or more of propylene glycol methyl ether acetate (PMA), ethylene glycol diacetate (EGDA), and propylene glycol diacetate (PGDA) in combination.
[0024] Furthermore, the weight ratio of liquid A to liquid B in the water-based coating is 5:1 to 6:1.
[0025] Secondly, the present invention provides a method for preparing the aforementioned water-based coating, comprising the following steps: Preparation of Solution A: Emulsion-type silicone aqueous dispersion resin, dispersant, maleic anhydride-grafted polypropylene wax emulsion, substrate wetting agent, and deionized water are sequentially added to a container and stirred at 300-500 rpm for 15-20 minutes to ensure uniform dispersion of all components. Then, elastomer-modified acrylic dispersion, water-based colorant, nano-alumina dispersion, and emulsifying corrugation additive are added. The stirring speed is increased to 800-1000 rpm and stirring continues for 30-40 minutes to ensure uniform mixing of all components. Finally, defoamer and thickener are added, and stirring continues for 10-15 minutes to obtain Solution A. Preparation of solution B: Add the film-forming aid to another container and stir at 200-300 rpm. Then add the dehydrating agent and stir and disperse at 300-500 rpm for 30-50 minutes. Then add the adhesion promoter and water-based isocyanate curing agent and continue stirring for 20-30 minutes to mix all components evenly to obtain solution B. When using, mix liquid A and liquid B evenly to obtain a water-based coating for tableware.
[0026] Furthermore, the weight ratio of liquid A to liquid B is 5:1 to 6:1.
[0027] Thirdly, this invention provides the application of the water-based coating in the manufacture of tableware or catering utensil products. Specifically, it is applicable to products such as bowls, plates, and tableware trays.
[0028] The present invention has the following beneficial effects: The water-based coating of this invention, through the interaction of its components, forms a unique surface microstructure that provides durable and reliable anti-slip properties. The low surface energy and highly cross-linked network of the silicone resin ensure excellent stain resistance and easy cleaning. Through the synergistic effect of wetting, adhesion, and cross-linking, it achieves extremely strong adhesion to plastic substrates. The nano-sized alumina dispersion, as a nano-reinforcing phase, works synergistically with wax microparticles to optimize the surface microstructure, jointly improving impact resistance and anti-slip effect. Thus, it achieves comprehensive performance that balances anti-slip, stain resistance, and high adhesion, meeting the needs of the tableware or catering utensil manufacturing industry for high-performance water-based environmentally friendly coatings.
[0029] The coating of this invention adopts a water-based environmentally friendly system, with extremely low VOCs, is safe and non-toxic, and the coating fully meets the high standards required for food contact materials. It is an advanced coating solution that combines high performance and environmental friendliness. Detailed Implementation
[0030] The following embodiments are provided to better understand the present invention and are not limited to the preferred embodiments described. They do not constitute a limitation on the content and scope of protection of the present invention. Any product that is the same as or similar to the present invention, derived by any person under the guidance of the present invention or by combining the features of the present invention with other prior art, falls within the protection scope of the present invention.
[0031] For experiments not specifically described in the examples, the procedures or conditions should be followed according to the conventional experimental procedures described in the literature in this field. Reagents or instruments whose manufacturers are not specified are all commercially available conventional reagent products.
[0032] The materials used in the embodiments and comparative examples of the present invention are described below, but are not limited to these materials: Emulsion-type silicone aqueous dispersion resin: solid content 38±2%, KW-8924, Kehuai Industrial (Shanghai) Co., Ltd.
[0033] Waterborne hydroxyl acrylic dispersion resin: solid content 45±2%, Huangshan Liangu New Material Technology Co., Ltd., Uacryl 1633.
[0034] Maleic anhydride-grafted polypropylene wax emulsion: solid content 40±0.5%, Emulsion 94340, Michael Men.
[0035] Elastomer-modified acrylic dispersion: hydroxyl value 110±8 mgKOH / g, SX-500-2, Kunshan Wanjie New Material Technology Co., Ltd.
[0036] Dispersant: Aqueous solution of polyether-modified styrene-maleic anhydride copolymer, solid content 40±2%, DISPERBYK-190, BYK Chemical.
[0037] Thickener: H-120, Puwei (Shanghai) New Materials Technology Co., Ltd.
[0038] Nanoscale alumina dispersion: particle size D50 is 150nm, solid content is 40%, Nanjing Tianxing New Materials Co., Ltd., TAD-HA40.
[0039] Water-based pigments: prepared in-house using the following method: S1. Add 35 parts by weight of deionized water, 4 parts by weight of dispersant (Disperbyk-2015, BYK) and 0.2 parts by weight of defoamer (Tego Airex 901W, Evonik) to the mixing tank, and stir at 450 rpm for 5 minutes until well mixed. S2. Slowly add 50 parts of titanium dioxide (food grade rutile titanium dioxide) while stirring at 300 rpm to prevent dust from flying. After adding, increase the speed to 700 rpm and disperse for 20 minutes. S3. After evenly dispersing, increase the rotation speed to 1000 rpm and disperse at high speed for 45 minutes; S4. Transfer to a horizontal grinder and grind to a fineness of <15μm; S5. Add 4 parts by weight of propylene glycol, and adjust the viscosity of the pigment paste to 50% solid content with deionized water at 500 rpm. Set aside.
[0040] Emulsifying corrugation additive: Haiyue (Qingyuan) New Materials Co., Ltd., HY-8082.
[0041] Substrate wetting agent: polyether siloxane copolymer, TEGO Wet 270.
[0042] Defoamer: Polyether siloxane copolymer emulsion containing fumed silica, with a polyether siloxane copolymer content of 20% by mass, TEGO Airex 902 W.
[0043] Waterborne isocyanate curing agent: 17.0±1%, Jiangsu Fuqisen New Material Co., Ltd., AQUAPU-379.
[0044] Dehydrating agent: Molecular sieve dehydrating agent, Guangdong Shunde Lishuda Chemical Co., Ltd., BF-5.
[0045] Adhesion promoter: Nanjing Jingtianwei Chemical Co., Ltd., KH560.
[0046] Film-forming aids: PMA and PGDA are compounded in a weight ratio of 1:2.
[0047] Polyethylene wax emulsion: solid content 40±0.5%, Emulsion 91240G, Michael Men.
[0048] The preparation methods of the water-based coatings in the examples and comparative examples include the following steps: Preparation of Solution A: Emulsion-type silicone aqueous dispersion resin was added to a stirred tank, and stirring was started at 400 rpm. Dispersant, maleic anhydride-grafted polypropylene wax emulsion, substrate wetting agent, and deionized water were added sequentially, and stirred for 20 minutes to ensure thorough and uniform dispersion of all components. Then, elastomer-modified acrylic dispersion, water-based colorant, nano-alumina dispersion, and emulsifying corrugation agent were added, and the stirring speed was increased to 1000 rpm, continuing stirring for 30 minutes to ensure uniform mixing of all components. Finally, defoamer and thickener were added, and stirring was continued for 15 minutes to obtain Solution A. Preparation of solution B: Add the film-forming aid to another mixing vessel and stir at 200 rpm. Then add the dehydrating agent and stir at 500 rpm for 30 minutes. Then add the adhesion promoter and water-based isocyanate curing agent and continue stirring for 30 minutes to ensure that all components are mixed evenly to obtain solution B. When using, mix liquid A and liquid B evenly to obtain a water-based coating.
[0049] Table 1: Composition and dosage of water-based coatings in Examples 1-3 and Comparative Examples 1-5 (by weight parts)
[0050] Relevant performance tests: Sample preparation: The water-based coating was prepared by mixing the examples and comparative examples at a weight ratio of 5:1 for liquid A and liquid B. A 100 mm * 100 mm * 3 mm polypropylene (PP) plastic sheet substrate was cleaned with anhydrous ethanol. The mixed coating was then applied to the substrate using air spraying. After leveling at room temperature for 10 minutes, the substrate was dried in a 60°C oven for 2 hours, followed by curing at room temperature for 24 hours to form a coating with a dry film thickness of approximately 35 μm. This coating was then set aside for various tests.
[0051] 1. Adhesion The test was conducted according to standard GB / T 9286-2021. The test method is as follows: Using a crisscross tool with a 1mm spacing, 6×6 squares were crisscrossed on the surface of the sample coating, cutting to the substrate. Debris was gently brushed away with a soft brush, and then 3M 610 pressure-sensitive adhesive tape was firmly applied, ensuring no air bubbles. The tape was then rapidly peeled off at a 60° angle within 1 minute. The extent of coating peeling in the crisscrossed areas was observed under a magnifying glass in a lighting box, and rated according to the standard from level 0 (intact) to level 5 (severe peeling). Level 0 is the best.
[0052] 2. Impact resistance The test was conducted according to standard GB / T 20624.2-2006. The test method is as follows: Using a drop hammer impact tester, the sample plate is placed face down on the impact table and fixed. A 1kg punch (12.7mm in diameter) is dropped freely from a certain height, impacting the back of the sample plate. The height is gradually increased, and after each test, the coating in the impact area is observed for cracking, peeling, or other damage. The maximum impact height (unit: cm) at which the coating is not damaged is recorded; the higher the value, the better the impact resistance of the coating.
[0053] 3. Anti-slip properties The test method is as follows: Using a static friction coefficient tester, fix the sample plate to the platform surface and place a standard stainless steel weight (with a standard rubber sheet as the base, total mass 200g) in the test area of the sample plate. Start the equipment to slowly tilt the platform at a uniform speed (1.5° / s). Accurately record the tilt angle of the platform at the instant the weight begins to slide using an angle sensor; this is the sliding angle. Repeat the test 3 times and take the average value. The smaller the sliding angle, the worse the anti-slip performance; the larger the sliding angle, the better the anti-slip performance.
[0054] 4. Stain resistance The test method is as follows: Add a few drops of the test liquid (soy sauce, vinegar, chili oil, mustard, red wine) to the surface of a horizontally placed sample plate, and immediately cover it with a watch glass to prevent evaporation. After standing for 24 hours at (23±2)℃, remove the watch glass, rinse with clean water, and wipe the test area dry with a soft, damp cloth. Observe the coating surface under diffused light. If visible changes such as discoloration, blistering, loss of gloss, or marks appear, it is rated as "fail"; if there are no changes, it is rated as "pass".
[0055] 5. Water boiling resistance The test method is as follows: Completely immerse the sample plate in distilled water at 90℃ for 45 minutes as one cycle. After completion, remove the sample plate, blot the surface moisture with filter paper, and allow it to recover under standard conditions for 1 hour. Observe whether the sample plate exhibits blistering, peeling, whitening, or other phenomena. Repeat this process for 20 cycles. If the sample plate shows no adverse changes after 20 cycles, it is rated as "pass"; otherwise, it is rated as "fail".
[0056] 6. Migration Test (1) Total migration: Tested according to standard GB 31604.8-2021; the total migration should be ≤10mg / dm³. 2 .
[0057] (2) Potassium permanganate consumption: Tested according to standard GB 31604.2-2016; the potassium permanganate consumption is required to be ≤10mg / kg; (3) Heavy metal (Pb) content: Tested according to standard GB 31604.9-2016; the heavy metal content is required to be ≤1mg / kg.
[0058] Table 2. Performance test results of waterborne coatings in Examples 1-3 and Comparative Examples 1-5
[0059] As can be seen from the above examples and comparative results, the water-based coating for tableware of the present invention can achieve a comprehensive performance of high adhesion, anti-slip properties, and stain resistance. It achieves an optimal grade of 0 in adhesion testing; exhibits excellent impact resistance (maximum impact height ≥ 55 cm without coating damage); demonstrates a sliding angle ≥ 35° in anti-slip testing; exhibits excellent stain resistance to all tested stains; passes the boiling water resistance test, making it suitable for mechanical cleaning methods such as dishwashers; and fully meets the high standards required for food contact materials, satisfying the demand for high-performance water-based environmentally friendly coatings in the tableware or catering utensil manufacturing industry.
[0060] Comparative Example 1, without the addition of maleic anhydride-grafted polypropylene wax emulsion, showed a significant decrease in impact resistance, slip resistance, and stain resistance, and its migration test failed to meet the standards for food contact materials.
[0061] In Comparative Example 2, the use of polyethylene wax emulsion instead of maleic anhydride-grafted polypropylene wax emulsion resulted in a deterioration in impact resistance, slip resistance, and stain resistance.
[0062] Comparative Example 3, which did not contain elastomer-modified acrylic dispersion, showed a sharp deterioration in adhesion and impact resistance, failed the stain resistance and boiling water resistance tests, and could not meet the food contact material standards in the migration test.
[0063] Comparative Example 4, without the addition of nano-alumina dispersion, showed a decrease in adhesion, impact resistance, and anti-slip properties.
[0064] In Comparative Example 5, the use of waterborne hydroxyl acrylic dispersion resin instead of emulsion-type silicone water dispersion resin resulted in a deterioration in adhesion, anti-slip properties, and water resistance.
[0065] The above embodiments are merely illustrative examples for clear explanation and are not intended to limit the implementation. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively list all possible implementations. However, obvious variations or modifications derived therefrom are still within the scope of protection of this invention.
Claims
1. A non-slip, water-resistant coating, characterized in that, Includes liquid A and liquid B; The A liquid comprises the following components by weight: 35-60 parts of emulsion-type organosilicon aqueous dispersion resin; 3-10 parts of maleic anhydride-grafted polypropylene wax emulsion. 5-10 parts elastomer-modified acrylic dispersion; 0.5-1.2 parts dispersant; 1-3 parts thickener; 3-8 parts nano-alumina dispersion; 15-25 parts water-based color paste; 0.3-1 part emulsifying ripple agent; 0.1-1 part substrate wetting agent; 0.1-1 part defoamer; 3-5 parts deionized water; The B liquid comprises, by weight, the following components: 90-100 parts of water-based isocyanate curing agent, 0.3-0.8 parts of dehydrating agent, 5-8 parts of adhesion promoter, and 2-5 parts of film-forming aid.
2. The water-based coating according to claim 1, characterized in that, The solid content of the emulsion-type organosilicon aqueous dispersion resin is 36%-40%; the solid content of the maleic anhydride grafted polypropylene wax emulsion is 34%-42%; and the hydroxyl value of the elastomer-modified acrylic dispersion is 100-120 mgKOH / g.
3. The water-based coating according to claim 1, characterized in that, The dispersant is selected from an aqueous solution of polyether-modified styrene-maleic anhydride copolymer; the solid content of the aqueous solution of polyether-modified styrene-maleic anhydride copolymer is 35%-45%.
4. The water-based coating according to claim 1, characterized in that, The thickener is selected from hydrophobic modified alkali-swelling thickeners; the particle size D50 of the nano-alumina dispersion is 120-150nm, and the solid content is 30%-40%; the water-based color paste is selected from food contact grade water-based color paste, and its solid content is 40%-60%; the emulsifying ripple agent is an organosilicon polymer emulsion; and the substrate wetting agent is selected from polyether siloxane copolymers.
5. The water-based coating according to claim 1, characterized in that, The defoamer is selected from polyether siloxane copolymer emulsion containing fumed silica; the mass content of polyether siloxane copolymer in the polyether siloxane copolymer emulsion containing fumed silica is 15%-25%.
6. The water-based coating according to claim 1, characterized in that, The NCO content of the aqueous isocyanate curing agent is 16%-18%.
7. The water-based coating according to claim 1, characterized in that, The dehydrating agent is selected from titanate dehydrating agents or molecular sieve dehydrating agents; the adhesion promoter is selected from γ-(2,3-epoxypropoxy)propyltrimethoxysilane; the film-forming aid is selected from one or more of propylene glycol methyl ether acetate PMA, ethylene glycol diacetate EGDA, and propylene glycol diacetate PGDA.
8. The water-based coating according to claim 1, characterized in that, The weight ratio of liquid A to liquid B is 5:1 to 6:
1.
9. A method for preparing a water-based coating as described in any one of claims 1-8, characterized in that, Includes the following steps: Preparation of Solution A: Emulsion-type silicone aqueous dispersion resin, dispersant, maleic anhydride-grafted polypropylene wax emulsion, substrate wetting agent, and deionized water are sequentially added to a container and stirred at 300-500 rpm for 15-20 minutes to ensure uniform dispersion of all components. Then, elastomer-modified acrylic dispersion, water-based colorant, nano-alumina dispersion, and emulsifying corrugation additive are added. The stirring speed is increased to 800-1000 rpm and stirring continues for 30-40 minutes to ensure uniform mixing of all components. Finally, defoamer and thickener are added, and stirring continues for 10-15 minutes to obtain Solution A. Preparation of solution B: Add the film-forming aid to another container and stir at 200-300 rpm. Then add the dehydrating agent and stir and disperse at 300-500 rpm for 30-50 minutes. Then add the adhesion promoter and water-based isocyanate curing agent and continue stirring for 20-30 minutes to mix all components evenly to obtain solution B. When using, mix liquid A and liquid B evenly to obtain a non-slip and water-resistant coating.
10. The application of the water-based coating according to any one of claims 1-8 in the manufacture of tableware or catering utensil.
Citation Information
Patent Citations
Anti-skid and anti-fouling tableware paint and preparation method thereof
CN111100533A
High-wear-resistant water-based plastic printing ink and preparation method thereof
CN108070294A
Hybrid dynamic polymer containing reversible free radical type dynamic covalent bonds and application thereof
CN111378183A
Hydrophobic polyolefin composition and preparation method thereof
CN112521685A
Cited By
Water-based matte antibacterial light-absorbing coating and preparation method thereof
CN122037758A
A waterborne matte antibacterial light absorbing coating and a method of making the same
CN122037758B